On the occurrence of the short-nosed tripod fish Triacanthus biaculeatus (Bloch, 1786) in the North of Basrah, Southern Iraq - Ghazi, A.H.; Al-Faisal, A.J.; Alfaris, M.A.A. (Mesopotamian Journal of Marine Sciences, 2021)
In this article, we report on the occurrence of the short-nosed tripod fish Triacanthus biaculeatus (Bloch, 1786) in the North of Basrah, West of Al-Dair district which was not reported in this region before. Two specimens were obtained in November 2018 and identified as, T biaculeatus. They have a total length ranged from 69.0 to 137.0 mm. The first dorsal fin has 5 spines, the second spine is much less than half the length of the first one. The ventral surface of the pelvis is slightly tapered to words the posterior end.